267 Supplementing Ca salts of soybean oil to late-gestating beef cows: Impacts on performance and physiological responses of the offspring. (30th November 2020) - Brandão, Alice; Cooke, Reinaldo F; Schubach, Kelsey; Rett, Bruna; Souza, Osvaldo; Pohler, Ky G; Bohnert, David; Marques, Rodrigo
Abstract: This experiment compared performance and physiological responses of the offspring from cows supplemented with Ca salts of soybean oil (CSSO) or prilled saturated fat (CON) during late gestation. Non-lactating, pregnant Angus × Hereford cows (n = 104) that conceived during the same fixed-time artificial insemination protocol, using semen from 2 sires, were used in this experiment. Cows were ranked by pregnancy sire, body weight (BW), and body condition score (BCS). On d 180 of gestation (d -15), cows were randomly assigned to receive (dry matter basis) 415 g of soybean meal per cow daily in addition to 1) 195 g/cow daily of CSSO (n = 52) or 2) 170 g/cow daily of CON (n = 52). Cows were maintained in 2 pastures (26 cows/treatment per pasture), and received daily 12.7 kg/cow (dry matter basis) of grass-alfalfa hay. From d 0 until calving, cows were segregated into 1 of 24 feeding pens thrice weekly and received treatments individually. Cow BW and BCS were recorded, and blood samples were collected on d -15 of the experiment and within 12 h after calving. Calf BW was also recorded and blood sample collected within 12 h of calving. Calves were weaned on d 290 of the experiment, preconditioned for 35 d (d 291 to 325), and transferred to a feedyard where they remained until slaughter. Upon calving, CSSO cows and calves had greater (P < 0.01) plasma concentrations of linoleic acid and total ω - 6 FA compared with CON cohorts. No differences in calf birth BW, weaning BW, and final preconditioning BW were noted (P ≥ 0.36) between treatments. Average daily gain and final BW in the feedlot were greater (P ≤ 0.05) in steers from CSSO cows compared with CON. The incidence of calves diagnosed with BRD that required a second antimicrobial treatment was less (P = 0.03) in calves from CSSO cows, resulting in reduced (P = 0.05) need of treatments to regain health compared with CON (Table 5). Upon slaughter, longissimus muscle area was greater (P = 0.03) in calves from CSSO cows compared with CON. Collectively, these results suggest that supplementing CSSO to late-gestating beef cows stimulated programming effects on postnatal offspring growth and Page 2 of 15 For Peer Review health. Therefore, supplementing late-gestating beef cows with CSSO appears to optimize offspring welfare and productivity in beef production systems.